The mtDNA D-Loop Legacy of Cattle: Fluctuations in Diversity from the Neolithic to Early Medieval Times in Switzerland - José Granado; Elizabeth Wright; Robert Blatter; Jürg Lange; Meral Turgay; Laura Bañuelos; Sabine Deschler-Erb; Barbara Stopp; Elisabeth Marti-Grädel; Marguerita Schäfer; Idoia Grau-Sologestoa; Sandra Ammann; et al. (Diversity, 2023)
Fluctuations in the size of taurine cattle (Bos taurus) have been regularly demonstrated using archaeozoological data from across time and space in Europe, and have been linked to cultural, social and economic changes, but little is known about whether phenotypic change is accompanied by changes in genetic diversity. Here, we performed PCR-typed analysis of the partial mtDNA d-loop fragments of 99 cattle from the Neolithic to Early Medieval times from a number of different sites across Switzerland, combining newly presented data with previously published data (n = 20). We found that most cattle included (84) were members of the common European macro-haplogroup T3. However, cattle belonging to the haplogroups T1, T2, Q and P were identified as early as the Neolithic period, before 2690 cal. BCE. The highest diversity was found in the Neolithic period, during the 1st century CE and during the 7th–8th centuries CE. Bottleneck phases with low genetic diversity were detected during the Late Iron Age and from the fifth to the seventh century CE. Based on the FST values, Horgen, Corded Ware and cattle populations from the seventh to the ninth century CE were plotted away from the clusters of all other populations. The periods with larger-sized cattle correspond with those of high mtDNA d-loop diversity. Phenotype and genotype both appear to respond to the same socio-economic and cultural processes.